Identification of sex-biased and gonadal developmental miRNAs during critical windows of early gonadal differentiation in the Chinese giant salamander (Andrias davidianus) - Shijun Yang; Xinlin Wang; Han Yang; Fan Yan; Lishan Xu; Zhijie Jian; Guangxiang Zhu; Qin Wang (BMC Genomics)
Abstract The Chinese giant salamander (CGS), Andrias davidianus, the largest living amphibian, is of significant conservation importance for its wild populations and serves as a valuable economic species in aquaculture. Given that male CGS are larger than female, understanding the mechanisms behind gonadal differentiation and development is critical for optimizing production in aquaculture. This study conducted small RNA-seq on male and female gonads during two key differentiation windows in CGS. PCA analysis revealed distinct clustering within groups and clear differentiation between groups. A total of 374 miRNAs were identified, including 162 known and 212 novel miRNAs. Differential expression and enrichment analysis across the two time points identified nine sex-biased miRNAs involved in CGS gonadal differentiation, including let-7b-3p, miR-3529-3p, miR-34c-5p, miR-10-5p, miR-7-5p, and four novel miRNAs, and network of these nine sex-biased miRNAs with their target genes were constructed. Furthermore, our findings suggest that male and female gonadal development processes are likely regulated by distinct miRNAs. This study provides a comprehensive analysis of sex-biased and gonadal development related miRNAs in CGS, offering a theoretical foundation for enhancing CGS aquaculture productivity through targeted sex ratio management.